2007
DOI: 10.1007/s00467-006-0283-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of microalbuminuria in postdiarrheal hemolytic uremic syndrome

Abstract: Patients who survive the acute phase of postdiarrheal hemolytic uremic syndrome (D+ HUS) may develop renal complications after years of apparent recovery. The optimal regimen for monitoring these children is unclear. We therefore determined if screening for microalbuminuria, in the absence of overt proteinuria at follow-up, increased the sensitivity for predicting long-term renal-related sequelae. We found that screening for microalbuminurea, within the first 6-18 months following an episode of HUS, increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Garg et al compared the presence of microalbuminuria in patients who had had HUS 3 years previously with an age-matched and gendermatched control group without HUS and concluded that a longer follow-up period is needed to determine if this finding has clinical relevance and utility [14]. Lou-Meda et al examined 35 patients with HUS and found that screening for microalbuminuria, within the first 6-18 months following an episode of HUS, improved the sensitivity for predicting later sequelae from 22% to 66.8%, compared to screening for overt proteinuria alone [15]. We agree with the authors that the clinical value of microalbuminuria as a predictor of long-term renal sequelae should be confirmed in a larger cohort with a longer period of follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…Garg et al compared the presence of microalbuminuria in patients who had had HUS 3 years previously with an age-matched and gendermatched control group without HUS and concluded that a longer follow-up period is needed to determine if this finding has clinical relevance and utility [14]. Lou-Meda et al examined 35 patients with HUS and found that screening for microalbuminuria, within the first 6-18 months following an episode of HUS, improved the sensitivity for predicting later sequelae from 22% to 66.8%, compared to screening for overt proteinuria alone [15]. We agree with the authors that the clinical value of microalbuminuria as a predictor of long-term renal sequelae should be confirmed in a larger cohort with a longer period of follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…There was no stratification of patients depending on the degree of proteinuria among individual studies. Another study found that screening for microalbuminuria, within the first 6-18 months following an episode of post-diarrheal HUS, increased the sensitivity for predicting later sequelae from 22 to 66.7%, compared to screening for overt proteinuria alone [13].…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the renal status of these children includes checking renal function and blood pressure and screening for proteinuria and albuminuria [21].…”
Section: Discussionmentioning
confidence: 99%